(untitled) (Kathmandu University Medical Journal, 2014)
Background Smoking and health are intimately related and thus, smoking among future health care personnel is an important issue. As future physicians and dentists who will witness the continued burden of smoking-related diseases among their patients, represent a primary target for smoking prevention programs. Objectives To explore the magnitude of smoking problem and assess the major causes aggravating the burden of smoking among medical and dental students. Methods A cross sectional study was conducted between June and July 2009 among 345 medical and dental students. Pre-tested self-administered questionnaire containing questions regarding smoking and its various correlates were used to collect the data. Chi square test was used for testing hypothesis. Results Prevalence of smoking was estimated as 38.4%, among whom majority started smoking during 15 to 19 years of life. Peer pressure was the major cause behind smoking (29.5%). Nearly one third of the participants used to consume alcohol along with smoking. Presence of parental smoking and use of other drugs were significantly associated with smoking among the students. Conclusion Tobacco smoking is a significant health problem among the male medical and dental students. Medical and dental students were approached as they are the treatment providers for smoking and disease related to it in the future. The results in our study are discouraging and reveal that the medical knowledge regarding ill effects of smoking has not been able to check its use. DOI: http://dx.doi.org/10.3126/kumj.v11i1.11020 Kathmandu University Medical Journal Vol.11(1) 2013: 32-36